Decentralization, Democratic Governance, and Civil Society in Comparative Perspective: Africa, Asia, and Latin America (The Johns Hopkins, 2004)
Decentralization, Democratic Governance, and Civil Society in Comparative Perspective studies the relation of decentralization to democratization at both intermediate and local levels and analyzes how decentralization is transforming the relationship between the state and civil society. This book presents case studies from six countries in three continents in which decentralization of some parts of government has been attempted: Mexico, Chile, South Africa, Kenya, the Philippines, and Indonesia.